2015
DOI: 10.1111/plb.12418
|View full text |Cite
|
Sign up to set email alerts
|

The plant secondary metabolite citral alters water status and prevents seed formation in Arabidopsis thaliana

Abstract: Based on previous results, which showed that the secondary metabolite citral causes disturbances to plant water status, the present study is focused on demonstrating and detailing these effects on the water-related parameters of Arabidopsis thaliana adult plants, and their impact on plant fitness. Clear evidence of effects on water status and fitness were observed: plants treated with 1200 and 2400 μm citral showed decreased RWC, reduced Ψs , increased Ψw and reduced stomatal opening, even 7 days after the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Taken together, the results obtained suggest that TC induced an alteration in water status followed by oxidative damage, as also observed by Moran et al (1994) for drought stress in pea plants. Graña et al (2015) found similar results for A. thaliana treated with citral. This hypothesis was also supported by altered leaf morphology (spiralisation) after exposure to the highest TC concentration.…”
Section: Phytotoxicity In Adult Plantssupporting
confidence: 87%
See 1 more Smart Citation
“…Taken together, the results obtained suggest that TC induced an alteration in water status followed by oxidative damage, as also observed by Moran et al (1994) for drought stress in pea plants. Graña et al (2015) found similar results for A. thaliana treated with citral. This hypothesis was also supported by altered leaf morphology (spiralisation) after exposure to the highest TC concentration.…”
Section: Phytotoxicity In Adult Plantssupporting
confidence: 87%
“…The increase in malondialdehyde, an end product of lipid peroxidation and indicative of cell damage; the decrease in protein content, probably due to the strong Zn 2+ content reduction, an essential element for protein biosynthesis (Eide 2006); and degradation of photosynthetic pigments sustain this hypothesis (Graña et al 2013b(Graña et al , 2015. Further, several elements affected by TC could be responsible for lipid peroxidation onset.…”
Section: Phytotoxicity In Adult Plantsmentioning
confidence: 95%
“…viscosa VOCs revealed a strong presence of monoterpenes and sesquiterpenes, well known as allelopathic compounds, able to affect plant growth generally causing oxidative stress followed by a cascade effect on many physiological processes of receptor plants [57]. Both of them affected mitochondrial respiration [58, 59] and microtubule distribution and organization [38, 60], destroyed cell membranes [61] and altered hormone balance and plant water status [36, 62]. The sesquiterpenes trans -caryophyllene was able to affect the germination and growth of several weeds as well as of Arabidopsis adult plants inducing the alteration of plant water status [36].…”
Section: Discussionmentioning
confidence: 99%
“…The sesquiterpenes trans -caryophyllene was able to affect the germination and growth of several weeds as well as of Arabidopsis adult plants inducing the alteration of plant water status [36]. Graña et al [62] observed similar effects with the monoterpene citral. Singh et al [63] reported that α- Pinene was able to inhibit root growth of several weeds causing oxidative stress and destroying cell membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation